Thermal Property Studies of In Situ Blended Graphene/Nature Rubber Nanocomposites - Zhenqiang Dong; Fei Cai; Zuming Jiang; Wanli Xu (International Journal of Polymer Science)
In this work, graphene/nature rubber (GE/NR) composites with filler content from 0 wt% to 1 wt% were prepared by an in situ reduction process. Thermal properties of the nanocomposites were studied by thermogravimetric (TG) analysis and thermogravimetric difference (ΔTG). Composites with higher GE content evidenced stronger thermal stability-enhancing effect. Kinetic analysis showed that the activation energies (Ea) during degradation of composites were always higher than pure NR. However, Ea reached its maximum at 0.1 wt% GE content and started to decrease with further increase in GE loading. The changes in the thermal properties were attributed to the chemical structure and heat transfer properties of graphene sheets.